A novel formula from mulberry leaf ameliorates diabetic nephropathy in rats via inhibiting the TGF-β1 pathway. Issue 10 (5th August 2015) - Zhang, Qichun; Lu, Ying; Ma, Zhi; Li, Yu; Guo, Jing; Meng, Qinghai; Bian, Huimin
Abstract : A novel formula derived from mulberry leaf ameliorates metabolic syndrome and kidney function of diabetic nephropathy rats. Abstract : Introduction : Based on the hypoglycemia and hypolipidemia of mulberry leaf and its extracts, we investigated the effect of a novel formula, Sang Tong Jian (STJ), from mulberry leaf on rats with diabetic nephropathy (DN). Methods : The DN rats were induced by a long-term high-fat diet and a single streptozotocin injection. STJ was introduced for 12 weeks from the presence of hyperglycemia. The fasting blood glucose of DN rats was determined at weeks 5, 7, 9, and 11 respectively. The serum GSP, GHb and lipid profiles were analyzed by using a colorimetric method and ELISA kits. The kidney function of DN rats was demonstrated through the analysis of urine creatinine, urine albumin, serum urea nitrogen, serum creatinine and the creatinine clearance rate. The H–E (haematoxylin and eosin) and PAS (Periodic Acid-Schiff) staining were adopted to exhibit the morphology of the kidney. The TGF-β1 and p-smad2/3, smad2/3, collagen IV, connexin 43 and E-cadherin were assayed via immunohistochemistry and western blot. Results : STJ significantly decreased the fasting blood glucose ( p < 0.01) and the glycation end product ( p < 0.05), and regulated dyslipidemia. Inhibition of the thickening of the glomerular basement membrane and amelioration of the kidney function were shown in STJ-treated DN rats. Moreover, STJ decreased the levels of TGF-β1, collagen IV, connexin 43 and activation of smad2/3 ( p < 0.01), and enhanced E-cadherin ( p < 0.01) in the kidney of DN rats. Conclusion : 12 week administration of STJ improved the metabolic parameters associated with blood glucose and lipid and inhibited the TGF-β1 signaling pathway, which positively contributed to the amelioration of chronic diabetic kidney disease.